The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12564-020-09649-7
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic habitus and new aspirations of higher education elites in transitional Myanmar

Abstract: This paper examines critical aspects of the birth of the new generation of Myanmar's emerging elite groups and their roles in the society based on in-depth qualitative research conducted in two universities in Yangon. It particularly pays close attention to the critical roles of the two universities -as political, social and knowledge institutions -in the formation of the new elite groups in Myanmar. The interplay between the students' individual agency and the two elite higher education institutes implies thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Given the challenges, the reforms within the HE sector were going quite well [56]. Despite the pandemic, the MOE went on to draft the NESP 2 where the vision of HE was set as: "By the end of NESP, students have equal opportunities to access and succeed in a worldclass HE system.…”
Section: Higher Education (He) and The Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the challenges, the reforms within the HE sector were going quite well [56]. Despite the pandemic, the MOE went on to draft the NESP 2 where the vision of HE was set as: "By the end of NESP, students have equal opportunities to access and succeed in a worldclass HE system.…”
Section: Higher Education (He) and The Reformsmentioning
confidence: 99%
“…"Part of the aim of the textbooks was to instil an understanding of "the Union" that conflates the state, nation, territory and people" [74] (p.1). Metro [75] (p. 56) showed that what she calls a "trinity of activities-national unification, economic development, and religious patronage" are carried out by the military regime, reflecting ancient Myanmar kings who are "hero-ised" in the textbooks. At universities, Bumanisation has been evident by the lack of inclusion of ethnic students, acknowledged by the MOE official at the second Myanmar HE conference in 2018 [7].…”
Section: Conflict: Clash Of Ideologiesmentioning
confidence: 99%
“…Simultaneously, the experiences in 1988 and 2007, both of which were caused by public demonstrations of democratisation after the mismanagement of economic issues by the junta, greatly influenced the climate in higher education, seriously repressing the autonomy and freedom of both students and faculty members (Hong and Kim, 2019). This repressive, authoritarian climate started to change due to various initiatives coming from the steps taken towards democratisation (Esson and Wang, 2016; Hong and Kim, 2019; Hong and Chun, 2021). That is, the students and adults involved, including teachers and teacher educators, started to enjoy slightly more relaxed conditions in the 2010s, even if they were unable to overtly discuss issues related to democratisation.…”
Section: Questions About the Purpose Of Teacher Educationmentioning
confidence: 99%
“…From the logical point of view, the elite can be influential in different areas [28] and can present efficient suggestions in different times [29]. Thereby, elite rule and participation in making decisions are favourable for every society provided they are not abused [30].…”
Section: Elitist Approach By Governments and Key Role Of Them In Soci...mentioning
confidence: 99%